Effectiveness of Traditional Game-Based Learning: using Panjat Pinang Context to Improve Students’ Mathematical Modelling Skills - Amarta, Nadiati; Darmawijoyo, Darmowijoyo; Hartono, Yusuf (Universitas Muhammadiyah Mataram, 2025)
This study aims to develop a context-based Learner Worsheet (LKPD) on comparison material using the traditional game of panjat pinang to enhance the mathematical modelling skills of seventh-grade junior high school. The research employed a design research approach with the Tessmer model, consisting of preliminary and formative evaluation stages. Instrument included expert validation sheets (to assess content, construct, and language), practicality questionnaires, and a mathematical modelling ability test (covering understanding tasks, mathematising, working mathematically, and explaining results). Data analysis involved calculating percentage scores for validity and practicality, along with descriptive analysis of students’ mathematical modelling performance. The results indicate that the LKPD achieved high validity with an average score of 84,77% and good practicality with an average score of 81,25%. Field testing demonstrated its potential to improve students’ performance in all four stages of mathematical modelling. In conclusion, integrating panjat pinang as a cultural context creates meaningful learning experiences, making the concept of comparison more accessible and engaging. The LKPD can serve as an effective alternative mathematics teaching material and a reference for developing other culturally relevant resources.